Dimensions of Sociology of Law The Urgency of Implementing Digital Transactions Towards the Era of Society 5.0 - Purborini, Vivi Sylvia; Suryanatha, Ida Bagus (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2024)
The Society 5.0 era brings major changes to Indonesia. This transformation also presents challenges, especially in terms of regulation, data security, and consumer protection. A deep understanding of the sociological dimensions of law is very important. In this article, the method used by the researcher is a qualitative descriptive method. In the research approach, the researcher uses a sociological legal approach. In the context of rapid technological developments and social change, the study of the sociology of law on the need to immediately carry out digital transactions is very relevant. The implementation of digital transactions is not only related to economic aspects, but also includes various important social and legal dimensions. The sociology of law sees that digital transactions represent a significant change in the way society interacts and transacts. This shift creates new opportunities, but also challenges, which require adjustments to legal regulations to remain relevant and responsive to the needs of society. In the context of Society 5.0, rapid changes in digital technology require the legal system to be responsive and flexible, so that it can answer the challenges that arise without hindering technological progress. The implementation of digital transactions towards the Society 5.0 era is not only an option, but a necessity to ensure sustainable economic growth, social inclusion, and effective legal protection. Therefore, collaboration between the government, private sector, and society is essential to create a digital transaction ecosystem that is safe, fair, and beneficial for all. The relationship between legal sociology, digital transactions, and the Society 5.0 era shows the importance of a multidisciplinary approach to understanding the social and legal impacts of digitalization.